MANDATORY RULES OF THE LAW ON CONCESSIONS AND PUBLIC PRIVATE PARTNERSHIP AND THE PRINCIPLE OF FREEDOM OF CONTRACTING (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
The Law on Concessions and Public-Private Partnership contains provisions that regulate the relations between the public partner and the private partner. These are basically mandatory provisions. In this regard, the party autonomy principle is quite limited. At the same time, the Law on Concessions and Public-Private Partnership refers to the complementary application of the Law on Obligations as a lex general legislation. The purpose of this paper is to analyze the degree of freedom of contracting in the contracts for public-private partnership. This analysis will be useful in the process of negotiating and drafting a specific public-private partnership contract, which will provide appropriate guidance for the parties how to act in that process.